Interplay of Capital Formation, Economic Growth, and Unemployment in India’s Post-Economic Reform Era: A Quantitative Study - Sinha, Jitendra Kumar (Journal of Advanced Research in Humanities and Social Sciences; Vol 11 No 2 (2024): Journal of Advanced Research in Humanities and Social Sciences, 2024)
Introduction: Gross Fixed Capital Formation (GFCF) is a critical pillar within domestic investment frameworks, wielding substantial influence over economic growth trajectories and unemployment dynamics. However, the nuanced relationships between investment, economic expansion, and employment remain subject to continual empirical scrutiny, yielding divergent conclusions. Despite India’s sustained but moderate investment and economic growth rates, the nation confronts persistent unemployment. This study explores the intricacies of investment, economic advancement, and employment within the Indian landscape, leveraging authoritative data from entities such as the Ministry of Statistics and Programme Implementation (MoSPI) and the Government of India. Method: Employing the Johansen Co-integration and Vector Error Correction Model (VECM) methodologies, this research endeavours to unravel the underlying interconnections among these variables. Data series after being converted to logarithms were subjected to find the integrated degree of the series. This was done through the augmented unit root testing using the Dickey-Fuller (ADF) and Phillips-Perron (PP) tests for both levels and the first difference of all the variables. Results: Findings unveil enduring relationships, underpinning bidirectional causality between employment levels and economic expansion. Notably, economic upswings serve as precursors to heightened investment endeavours, underscoring their catalytic role in fostering employment opportunities over prolonged periods within India. Furthermore, the study corroborates the notion of jobless growth prevalent in the post-economic reform era. Conclusion: It accentuates the urgency of cultivating a more conducive economic milieu via augmented infrastructural undertakings and diversification strategies, especially in labour-intensive domains like agriculture and allied sectors. Such strategic interventions emerge as imperative for bolstering investment inflows and ameliorating the prevailing unemployment conundrums gripping the nation.